Does surgeon seniority affect adhesion assessment at cesarean delivery? A prospective studyAJOG Global Reports at a Glance - Shai Ram, MD; Ziv Shapira; Hila Shalev-Ram; Shira Alon; Roza B. Shperling; Margaret J. Lipinski; Yariv Yogev; Ariel Many (Elsevier, 2023)
BACKGROUND: Intraabdominal adhesions may develop following cesarean delivery and are considered a major concern. OBJECTIVE: This study aimed to determine the effect of surgeon seniority in evaluating intraabdominal adhesions at cesarean delivery. STUDY DESIGN: A prospective study to estimate interrater reliability between surgeons was conducted. Women who underwent cesarean delivery (January-July 2021) in a single tertiary university-affiliated medical center were included. Blinded questionnaires assessing adhesions were completed by the surgeons. Questions were limited to 4 main anatomic sites and 3 possible categories of adhesion (each site was scored between 0 and 2; the sum score range was 0-8). The surgeons were ranked by increasing seniority (1-4) as: (1) junior residents (less than half of residency completed), (2) senior residents (more than half of residency completed), (3) young attending physicians (attending physicians for <10 years), and (4) senior attendings (attending physicians for >10 years). The weighted percentage of agreement was calculated between the 2 surgeons assessing the same adhesions. Scoring differences between the 2 surgeons (senior vs less senior) were also calculated. RESULTS: A total of 96 pairs of surgeons were included in the study. The sum interrater reliability found in the weighted agreement tests between surgeons was 0.918 (confidence interval, 0.898-0.938). When scoring differences between surgeons (senior vs less senior) were calculated, nonsignificant difference was found (mean sum score difference of 0.09 with a standard deviation of 1.03 in favor of the more experienced surgeon). CONCLUSION: Surgeon seniority does not affect subjective scoring of adhesion reports.